THE ROLE OF DIMUNITIVENESS IN LINGUISTICS (Conferencea, 2024)
This thesis provides a comprehensive overview of the role of diminutives in linguistics, drawing on cognitive, grammatical, and sociolinguistic perspectives to highlight the significance of diminutives in shaping language systems and communication patterns.